A new look at Thai AIDS : perspectives from the margin. - Fordham, Graham (Fertility, reproduction, and sexuality., 2005)
"Based on long-term ethnographic research in Northern Thailand and drawing on an extensive corpus of English and Thai language social science and medical HIV/AIDS literature, this book makes an in-depth study of the social construction of Thailand's HIV/AIDS epidemic. It addresses concepts and issues such as risk groups, risk behavior, alcohol use, gender and class, masculinity, the scapegoating of female prostitutes and men in the underclass, the reporting of the HIV/AIDS epidemic in Thailand's Thai language print media, and sexual activity amongst Thai youth. The book offers a sustained and powerful criticism of the limitations of the normative model of the Thai AIDS epidemic and, in its aim of promoting critically reflexive AIDS research techniques in order to produce a better understanding of issues 'on the ground' and hence more effective AIDS interventions, speaks not only to the Thai AIDS epidemic but to AIDS epidemics throughout Southeast Asia and elsewhere."--Jacket.